The Impact of Pernyataan Standar Akuntansi Keuangan 68 Application Guidelines for Banking Sector Issued by Otoritas Jasa Keuangan (OJK) - Mercedes Daimler Benz Ernanda; Angellifa Trinida Chairunnisa; Sabrina Puspa Ardani (AIBPM Publisher, 2022)
This study will discuss the impact of PSAK 68 application guidelines in banking sectors related to fair value measurement in Indonesia. Otoritas Jasa Keuangan (OJK) issued the Pernyataan Standar Akuntansi Keuangan (PSAK) 68 application guidelines for the banking sector during the COVID-19 pandemic in order to support the implementation of PSAK 68 from Ikatan Akuntan Indonesia (IAI) regarding fair value measurement. The PSAK 68 application guidelines encourage banks to present financial statements that accurately represent the company's actual financial position and financial performance by measuring the fair value based on facts. This study uses qualitative methods by evaluating the application of fair value disclosure with the asset valuation of banking sector companies in Indonesia. This study concluded that the guidelines issued by OJK have an impact on banking entities in maintaining the company's financial position during the pandemic and can encourage the growth of the banking sector in a sustainable manner. Keywords: Banking sector, fair value measurement, financial performance, financial position, PSAK 68